DI-012 Safety profile of janus associated kinase inhibitors. (14th February 2016) - Morgado, M; Santos, D; Rama, AC Ribeiro; Alcobia, A
Abstract : Background: Janus associated kinase family (JAK 1, JAK 2, JAK 3 and Tyk2) are molecular targets for enzyme inhibition that represent a useful strategy for the treatment of different clinical conditions, such as arthritis, psoriasis, organ rejection and multiple cancer types. However, JAK inhibitors are associated with major adverse drug reactions (ADR), which underlines the importance of close monitoring by healthcare professionals. Purpose: The aim of this study was to review all JAK inhibitors that are available on the pharmaceutical market, their therapeutic indications, their underlying mechanism of action and ADR, in order to improve pharmaceutical counselling. Material and methods: Literature review of summary of product characteristics of JAK inhibitors and literature sources from PubMed by searching the terms: 'JAK inhibitors', 'Janus associated kinases inhibitors' and 'Janus kinases inhibitors'. Drug databases of the European Medicines Agency (EMA) and United States Food and Drug Administration (FDA) were also consulted. Results: Currently, only ruxolitinib and tofacitinib are available on the pharmaceutical market. Ruxolitinib is a selective inhibitor of JAK1 and JAK2 indicated for the treatment of myelofibrosis and polycythaemia vera which is still a medicinal product subject to additional monitoring. Tofacitinib is a non-selective JAK inhibitor indicated for the treatment of rheumatoid arthritis, only authorised by the FDA with major warnings. Apart from the major haematological and immune adverse effects related to both drugs, interactions with other drugs may occur. Consequently, close analytical and clinical monitoring is required for better and correct use of these drugs. Conclusion: JAK inhibitors currently available on the pharmaceutical market have proven benefits in the treatment of oncologic and autoimmune diseases, but have significant ADR. Knowledge of these undesirable effects is an important factor for pharmacists to give proper information and advice to health professionals and patients regarding the correct and safe use of these drugs. On the other hand, it is important that healthcare professionals are alert to the pharmacodynamic profiles of these new drugs and report any suspected adverse reactions. References and/or Acknowledgements: We would like to thank all the physicians in our hospitals who collaborated with us. No conflict of interest.